Target organ damage in stress-induced arterial hypertension - O. N. Antropova; I. V. Osipova; N. А. Lobanova; K. I. Shakhmatova (Кардиоваскулярная терапия и профилактика, 2009)
Aim. То investigate the features of target organ damage in patients with stress-induced arterial hypertension (AH).Material and methods. The study included 329 men, aged 29—55 years, with Stage I-II AH. Group I consisted of 197 individuals with workplace AH (WAH), Group II — of 132 patients with essential AH (AH); mean age was 41,3±1,4 and 42,5±1,5 years, respectively. All participants underwent Doppler echocardiography and brachiocephalic (BC) duplex scanning.Results. Left ventricular hypertrophy (LVH) was diagnosed in 38,1 % and 28,1 % of the patients from Groups I and II, respectively. Concentric LVH (CLVH) prevalence was 12,3 % higher in WAH individuals than in AH patients (χ2=7,9; p=0,05). Type I diastolic dysfunction (DD) was registered in 87,3 % and 62,1 % of the patients from Groups I and II, respectively. DD prevalence was 25,2 % higher in WAH subjects than in AH participants (χ2=28,5; p=0,001). In Groups land II, increased thickness of common carotid artery wall was observed in 47,2 % and 34,1 %, respectively; its prevalence was 13,1 % higher in WAH patients comparing to people with AH.Conclusion. In WAH and AH patients, DD and LVH were the most typical manifestations of TV damage. DD was more prevalent in WAH than in AH. LVH prevalence was similar in both groups, but CLVH was more typical for WAH than for AH. The same tendency was observed for BC atherosclerosis.